2022
DOI: 10.56532/mjsat.v2i4.96
|View full text |Cite
|
Sign up to set email alerts
|

Grading System Prediction of Educational Performance Analysis Using Data Mining Approach

Abstract: In the neoteric century, education holds the key to bringing tremendous upgradation to the world. In most Asian countries, it is very challenging to apply education data mining techniques due to the variety of institutional data categories. In this research, an efficient data collection technique has been designed to gather institutional data, analyse and pre-process the data and apply specific data mining methods to estimate students’ progress. A real-time dataset has been designed from student transcript dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…On the other hand, it has been observed that some studies that have used datasets from LMSs platforms get a little higher prediction accuracy than what has been achieved using MOOCs datasets, the accuracy prediction through using of dataset from LMSs platforms range between 67.2% and 97%, with an average of 85.1% (see Figure 13). The LMS's average accuracy is a little less than that of MOOCs, which may be due to some studies that did not provide a numeric prediction accuracy of their models Prabowo et al (2021); Rahman et al (2022); Tao et al (2022). Another reason is that a considerable number of studies have low prediction accuracy compared to the studies using MOOCs datasets.…”
Section: Dataset Used In Predictive Modelsmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, it has been observed that some studies that have used datasets from LMSs platforms get a little higher prediction accuracy than what has been achieved using MOOCs datasets, the accuracy prediction through using of dataset from LMSs platforms range between 67.2% and 97%, with an average of 85.1% (see Figure 13). The LMS's average accuracy is a little less than that of MOOCs, which may be due to some studies that did not provide a numeric prediction accuracy of their models Prabowo et al (2021); Rahman et al (2022); Tao et al (2022). Another reason is that a considerable number of studies have low prediction accuracy compared to the studies using MOOCs datasets.…”
Section: Dataset Used In Predictive Modelsmentioning
confidence: 94%
“…A study by Rahman et al (2022) suggested a strategy for gathering institutional data, analyzing and preprocessing the data, and using DNNs to estimate student's progress and the final CGPA. To analyze the prediction of student quality, a realtime dataset was created from student transcript data from a reputable university in Bangladesh.…”
Section: Deep Neural Network (Dnns)mentioning
confidence: 99%